Origanum vulgare Essential Oil vs. a Commercial Mixture of Essential Oils: In Vitro Effectiveness on Salmonella spp. from Poultry and Swine Intensive Livestock - Di Vito, Maura; Cacaci, Margherita; Barbanti, Lorenzo; Martini, Cecilia; Sanguinetti, Maurizio; Benvenuti, Stefania; Tosi, Giovanni; Fiorentini, Laura; Scozzoli, Maurizio; Bugli, Francesca; Mattarelli, Paola (Antibiotics (Basel), 2020)
Salmonella spp. represent a public health concern for humans and animals due to the increase of antibiotic resistances. In this scenario, the use of essential oils (EOs) could be a valid tool against Salmonella contamination of meat. This work compares the in vitro effectiveness of an Italian mixture of feed additives based on EOs (GR-OLI) with EO of Origanum vulgare L., recently admitted by European Food Safety Authority (EFSA) for animal use. Twenty-nine Salmonella serotypes isolated from poultry and pig farms were used to assess GR-OLI and O. vulgare EO antimicrobial propeties. O. vulgare EO was active on the disaggregation of mature biofilm, while GR-OLI was capable of inhibiting biofilm formation and disaggregating preformed biofilm. Furthermore, GR-OLI inhibited bacterial adhesion to Caco-2 cells in a dose-dependent manner. Both products showed inhibition of bacterial growth at all time points tested. Finally, the synergistic action of GR-OLI with commonly used antibiotics against resistant strains was investigated. In conclusion, the mixture could be used both to reduce the meat contamination of Salmonella spp. before slaughter, and in synergy with low doses of ciprofloxacin against resistant strains. Although EOs as feed additives are already used in animal husbandry, no scientific study has ever highlighted their real antimicrobial potential.